Misery bay [compact disc, unabridged] - Hamilton, Steve, 1961- (Hamilton, Steve, 1961- Alex McKnight novel., 2011)
Two months after an apparent suicide in a place known as Misery Bay, PI Alex McKnight is asked for help from his professional nemesis Sault Ste. Marie police chief Roy Maven. What seems like a simple quest to find a few answers will turn into a nightmare of sudden violence and bloody revenge, and a race against time to catch a ruthless and methodical killer.